2020
DOI: 10.7189/jogh.10.020402
|View full text |Cite
|
Sign up to set email alerts
|

Association between food insecurity and cardiometabolic risk in adults and the elderly: A systematic review

Abstract: Background Food insecurity is a public health concern that affects health and quality of life, but its association with cardiometabolic risk is not well established. Thus, this systematic review evaluated the association between food insecurity and cardiometabolic risk factors in adults and the elderly. Methods Search was conducted according to the PRISMA protocol using Scielo, LILACS and PubMed databases. We included original articles published in Portuguese, English, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
5
18
0
1
Order By: Relevance
“…Food insecure participants had higher BMI and waist circumference, blood pressure, fasting glucose, triglycerides, and LDL cholesterol, and lower HDL cholesterol. These ndings are in agreement with ndings of recent meta-analyses indicating a direct relationship of food insecurity with cardiometabolic risk factors, especially excess weight, hypertension, and dyslipidemias [12,34]. These abnormalities in metabolic and cardiovascular risk markers gradually progress during the lifespan and eventually leads to cardiovascular and other chronic diseases [7].…”
Section: Food Insecurity and Cardiometabolic Risk Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…Food insecure participants had higher BMI and waist circumference, blood pressure, fasting glucose, triglycerides, and LDL cholesterol, and lower HDL cholesterol. These ndings are in agreement with ndings of recent meta-analyses indicating a direct relationship of food insecurity with cardiometabolic risk factors, especially excess weight, hypertension, and dyslipidemias [12,34]. These abnormalities in metabolic and cardiovascular risk markers gradually progress during the lifespan and eventually leads to cardiovascular and other chronic diseases [7].…”
Section: Food Insecurity and Cardiometabolic Risk Factorssupporting
confidence: 91%
“…The questionnaire contains 9 items and has been translated and validated for use in Iranian community [20]. The HFIAS scale scores the food insecurity from 0 to 27 and categorizes it into 4 levels of food secure (0-1), and mild (2-8), moderate (9)(10)(11)(12)(13)(14), and severe (15-27) food insecure conditions. Anthropometric measurements.…”
Section: Page 3/18mentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found more obesity in urban areas (37.45%) than in rural areas (18%), while dyslipidemia was diagnosed more commonly in rural areas (44.54%) than in urban areas (13.51%). These results may reflect the finding that, although in general individuals of urban and rural areas have similar eating habits in our study, there were more men who eat fast food in rural areas.This agrees with the fact that the consumption of unsaturated fats is related to the suffering of dyslipidemia [9].…”
Section: Concomitant Diseases and Conditionssupporting
confidence: 90%
“…A systematic review by da Silva Miguel et al that evaluated the association between food insecurity and cardiometabolic risk factors concluded that there was a direct association between food insecurity and hypertension after adjusting for sociodemographic, economic, and lifestyle characteristics [ 24 ]. We did not identify longitudinal or interventional studies regarding food insecurity and hypertension.…”
Section: Resultsmentioning
confidence: 99%